Public- and private-good values of statistical lives: Results from a combined choice-experiment and contongent-valuation survey - Jon Strand (University of Oslo, Department of Economics, 2001)
We present a stated-preference study where values of statistical lives (VSL) are derived both as public and private goods, and we distinguish between three different death causes, heart disease, environmentally related illnesses and traffic accidents. 1000 randomly chosen individuals in Norway were faced a three-part valuation procedure: 1) pairwise comparisons (conjoint analysis), 2) combined contingent-ranking and contingent-valuation of willingness to pay (WTP) for public projects to reduce overall population mortality risk, and 3) WTP for individual treatment reducing own mortality risk from heart disease. Parts 1-2 comprise all three death causes, and indicate public-good VSL in the range 3-6 million USD, with heart disease deaths in the lower part of this range, environmental causes in the upper part, and traffic accidents in-between. Part 2 also permits a splitting up of VSL into motives (selfmotivated and altruistic), and indicates that about 30 % of total public-good WTP is selfmotivated. Part 3 provides a self-motivated (private-good) VSL figure for heart disease in the range 1-1.5 million USD, close to the self-motivated share of VSL from part 2. We find high consistency between values derived, and indications that private- and public-good VSL may differ subtantially, as well as VSL by death cause. Under pairwise comparisons in part 1 we find complete insensitivity of VSL to risk magnitude (or “scope”), in contrast to existing literature. The more complex choices under part 2 by contrast imply considerable scope sensitivity.
Keywords: H41; H42; I18; D64; 330; value of statistical lives; public goods; stated preference methods; altruism; Öffentliches Gut; Willingness to pay; Offenbarte Präferenzen; Meinungsforschung; Theorie; Wert des Lebens